C5 and C6 human dermatomes: a clinical, electromyographical, imaging and surgical findings Dermátomos humanos C5 e C6: estudo clínico, eletromiográfico, de imagem e cirúrgico - Antonio Tadeu de Souza Faleiros; Luiz Antonio de Lima Resende; Marco Antonio Zanini; Heloisa Amélia de Lima Castro; Roberto Colichio Gabarra (Arquivos de Neuro-Psiquiatria)
There is substantial controversy in literature about human dermatomes. In this work, C5 and C6 superior limb dermatomes were studied. The method consisted of comparing clinical signs and symptoms with conduction studies, electromyographical data, neurosurgical findings, and imaging findings obtained by computerized tomography (CT) or magnetic resonance imaging (MRI), for each patient. Data analysis from superior members in 18 patients suggests that C5 is located in the lateral aspect of the shoulder and arm, and C6 in the lateral aspect of the forearm and 1st, 2nd, and 3rd fingers. To our knowledge this is the first time that C5 and C6 human dermatomes have been studied by all the following methods together: clinical, electromyographical, CT and MR imaging, and surgical findings. Há controvérsias na literatura sobre os dermátomos humanos. Neste estudo os dermátomos do membro superior C5 e C6 foram analisados. O método consistiu em comparar os sinais e sintomas com achados eletromiográficos, de imagem e achados cirúrgicos. Análise dos dados do membro superior de 18 pacientes sugere que o dermátomo C5 esteja localizado na região lateral do ombro e braço, e o dermátomo C6 na região lateral do antebraço e 1º, 2º e 3º dedos da mão. Este é o primeiro estudo em que os dermátomos C5 e C6 foram avaliados pelos dados clínicos, eletromiográficos, de imagem e achados cirúrgicos.